“Factors Influencing Picky Eating in Toddlers in the Work Area of Madising Na Mario Community Health Center, Parepare City” - M. NATSIR (International Journal of Multidisciplinary Research and Studies, 2023)
Due to the considerable and quick growth and development that takes place during this time, the early years of a child's life are frequently referred to as the "golden period." Children are still incredibly reliant on their caretakers during this time to provide for their basic requirements, including food. Picky eating is a commonly encountered feeding problem in children during this developmental period. Several factors influence this condition. Understanding these factors can help parents and healthcare providers develop effective strategies to improve a toddler's eating habits and promote healthy growth and development. The objective of this study is to examine the relationship between picky eating and variables including appetite, maternal parenting style, infant and toddler feeding routines, and toddler psychology, using an analytical survey with a cross-sectional design. The results reveal a significant relationship between parenting style and feeding practices with picky eating in toddlers. However, there was no significant association between appetite and toddler psychology with picky eating. In conclusion, implementing a continuous parenting style model, and paying attention to both the parents and child's feeding practices, can help to ensure that the child's nutritional needs are met and prevent the occurrence of picky eating.